2008 IEEE Symposium on Computers and Communications 2008
DOI: 10.1109/iscc.2008.4625764
|View full text |Cite
|
Sign up to set email alerts
|

Metrics applied to Aspect Oriented Design using UML profiles

Abstract: The Aspect Oriented Design (AOD) surges from the continuous search of improving the software systems development. The AOD is a methodology that emerges form the Aspect Oriented Programming (AOP), which intents to improve the concerns of the components in software programming; this methodology is based on existing technologies like Object Oriented (OO). Calculate the resources, is an activity that can improve the software development, because of this there are a big amount of investigation made on metrics. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…The results showed that there is not improvement in all design pattern, it depends on the current problem type some of them improved other not. [29] This paper has been tested aspect oriented programming using UML profile techniques. They used same OOP metrics that suitable for AOP.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that there is not improvement in all design pattern, it depends on the current problem type some of them improved other not. [29] This paper has been tested aspect oriented programming using UML profile techniques. They used same OOP metrics that suitable for AOP.…”
Section: Methodsmentioning
confidence: 99%
“…The works in [20][21][22] show the versatility of profiles to define different environments (application domains), which extend the UML specification (not only the syntax but also the semantic through formal OCL constraints). In particular, the work in [20] shows the way for defining design patterns with profile, proposing architecture in levels.…”
Section: Related Workmentioning
confidence: 99%
“…The work in [22] shows the definition of the C&K metrics applied to Aspect Oriented Design (AOD) using UML profiles. A new definition of metrics using profiles without modifying the OMG metamodels is specified.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many aspect-oriented metrics have been proposed (Apel et al, 2006;Debnath et al, 2008;Kumar et al, 2008;Lopez-Herrejon, 2006;Munnelly et al, 2007;Ortiz et al, 2008;Srivisut and Muenchaisri, 2007), there are few research studies that have explored the relationships between aspect-oriented metrics and external software quality attributes (Burrows et al, 2010;Sant'Anna et al, 2003;Shen et al, 2008;Tonella and Ceccato, 2005). Table X summarizes those studies by listing the relevant metrics and the external software quality attributes against which they were empirically evaluated.…”
Section: Related Workmentioning
confidence: 99%